Needs Analysis on The Infusion of Eco-Literacy in English Reading: MNC University Students’ Voice - Neni Nurkhamidah; Priskila Go (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
In response to the growing call for sustainable development and climate education, particularly in alignment with Sustainable Development Goal 13, this study explores students’ needs regarding the infusion of eco-literacy into English reading instruction. Although environmental themes have been introduced in the curriculum, little is known about how students experience and respond to eco-literacy in reading classes, which serve as a key input skill in language learning. This research aims to fill that gap by investigating the learning needs of English Education students at MNC University. Using a qualitative descriptive design, data were collected through open-ended questionnaires and semi-structured interviews. Thematic analysis was conducted to identify key patterns in participant responses. The results revealed six major themes: (1) Environmental Awareness & Responsibility, (2) Language Development, (3) Relevance & Real-Life Connection, (4) Engaging & Interactive Learning, (5) Student-Centered Learning, and (6) Variations of Topic. Participants preferred reading materials that are environmentally relevant, cognitively engaging, and linguistically accessible. These findings indicate that eco-literacy can enrich English reading instruction by fostering both language competence and environmental awareness. The study highlights the importance of designing student-centered, contextually relevant materials to ensure meaningful integration of sustainability in language education.